2016
DOI: 10.1021/acsomega.6b00146
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Driven and Full-Color-Tunable Fiber Source: Toward Next-Generation Clinic Fiber-Endoscope Tomography with Cellular Resolution

Abstract: In many biomedical applications, broad full-color emission is important, especially for wavelengths below 450 nm, which are difficult to cover via supercontinuum generation. Single-crystalline-core sapphires with defect-driven emissions have potential roles in the development of next-generation broadband light sources because their defect centers demonstrate multiple emission bands with tailored ligand fields. However, the inability to realize high quantum yields with high crystallinity by conventional methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…Another good example of a radially structured metamaterial waveguide is a hybrid-glass metamaterial fiber, which was reported for nonlinear effects [70]. This waveguide is fabricated by a laser-based fiber drawing technique [71,72]. To fabricate such a waveguide, sapphire (α − Al 2 O 3 ) was taken as a seed dielectric core and dendrite crystalline γ − Al 2 O 3 was deposited on it.…”
Section: Radially Structured Waveguidementioning
confidence: 99%
“…Another good example of a radially structured metamaterial waveguide is a hybrid-glass metamaterial fiber, which was reported for nonlinear effects [70]. This waveguide is fabricated by a laser-based fiber drawing technique [71,72]. To fabricate such a waveguide, sapphire (α − Al 2 O 3 ) was taken as a seed dielectric core and dendrite crystalline γ − Al 2 O 3 was deposited on it.…”
Section: Radially Structured Waveguidementioning
confidence: 99%
“…This approach helps laser processing and allows enhancing the structural characteristics of the single-crystal fiber produced. Similarly, in the last 10 years, cladded, single-crystalline fibers, mainly used as amplifiers, have been produced from bulk crystal seeds covered by Sol-Gel or embedded into silica or borosilicate hollow tubes, among other coating approaches [35][36][37][38][39]. Furthermore, some works from Rutgers University (Piscataway, NJ, USA) reported the growth from Pt wires together with the use of seed crystals or presintered ceramics as feed rods [40][41][42].…”
Section: Experimental Procedures (Standard)mentioning
confidence: 99%
“…[97], demonstrating the suitability of the fibers produced to be successfully employed for high-temperature sensing, as Ye et al, in 2005 [57], also similarly tested later for YAG:Cr 3+ . Likewise, Lai et al in 2016 grew borosilicate-cladded, single-crystalline-core sapphire fibers suitable to be employed in biomedical applications, such as light sources for endoscopy [39]. It must be highlighted that Lai et al, in 2018, also demonstrated a facile and scalable approach for the transformation of a centrosymmetric sapphire (α-Al 2 O 3 ) crystal to a large-scale 3D metamaterial (Si 4+ :γ-Al 2 O 3 ) with sub-wavelength fine structures [104].…”
Section: Materials For Photonic and Optical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of technology, more methods could be used to assess bone microarchitecture and mineral composition. Conventional X-ray diffraction (XRD) can give direct information about the crystalline quality and size as well as the presence of defects in the crystal ( Lai et al, 2016 ). In terms of evaluating bone mineralization, quantitative backscattered electron imaging (qBEI), quantitative magnetic resonance (QMR), micro-computed tomography (μCT), Fourier-Transform Infrared Spectroscopy (FTIR), and Raman spectroscopy analysis (RS) can be used to quantify the degree of bone mineralization and obtain bone microstructure data with different resolutions ( Donnelly, 2011 ).…”
Section: Introductionmentioning
confidence: 99%